The Development of KWL Plus Learning Activities in Economics of MathayomSuksa 1 - Pantuwong, Ratiporn; Rittidet, Prasopsuk; Suikraduang, Arun (Journal for Developing the Social and Community, 2023)
This research was aimed to ; (1) development of KWL Plus learning activities on Demand Supply and Financial Institutions of the Thai Economy of Mathayom Suksa 1. ; (2) compare the learning achievement before and after learning by KWL Plus learning activities on Demand Supply and Financial Institutions of the Thai Economy of Mathayom Suksa 1. ; (3) compare the analytical thinking by using KWL Plus learning activities before and after of Mathayom Suksa 1. ; (4) compare the student satisfaction on the KWL Plus learning activities of Mathayom Suksa 1. The research sample was consisted of 28 Mathayom Suksa 1 students, obtained through the cluster random sampling technique. The instruments used for this research included the activities lesson plan, analytical thinking ability test and learning satisfaction questionnaire. The statistics for data analysis were mean, standard deviation, and t - test (Dependent samples) The findings were as follows ; (1) the development of KWL Plus learning activities on Demand Supply and Financial Institutions of the Thai Economy is suitable in the most suitable criteria. ; (2) the learning achievement with KWL Plus learning activities was higher than before learning at .05 level of significance. ; (3) the analytical thinking ability of students who receive the KWL Plus learning activities was higher than before learning at .05 level of significance and ; (4) the student’ satisfaction on the KWL Plus learning activities was at a high level.